2021
DOI: 10.1016/j.jhazmat.2020.124693
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide and persulfate activation using UVA-UVB radiation: Degradation of estrogenic compounds and application in sewage treatment plant waters

Abstract: In the present work, the degradation of three estrogens (17β-estradiol (E2), estrone (E1) and 17α-ethinylestradiol (EE2)) was investigated under photoactivation of hydrogen peroxide and persulfate. Lab-scale irradiation experiments showed that both UVA and UVB radiations are able to photoactivate the oxidant precursors, although UVB is more efficient to generate radicals and therefore to degrade the targets. The efficiency of both oxidant precursors was investigated showing higher efficiency in the system with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…ranges from 2.2 ± 0.2 × 10 -5 to 3.0 ± 0.2 × 10 -4 cm 2 mJ -1 under UVA and from 9.4 ± 0.4 × 10 -4 to 1.1 ± 0.1 × 10 In the UVA/H 2 O 2 process, goes from 2.2 ± 0.2 × 10 -5 to 3.5 ± 0.3 × 10 -5 cm 2 mJ -1 with 46 to 64% of the degradation achieved by oxidation. These close results are attributed to similar photolysis constants of the estrogens (Table 7) and similar second order rate constants (from 1.8 to 2.9 × 10 10 M -1 s -1 ) between HO • and the estrogens [9]. When using S 2 O 8…”
Section: Estrogen Degradation In Drinking Water In Various Aopssupporting
confidence: 62%
See 1 more Smart Citation
“…ranges from 2.2 ± 0.2 × 10 -5 to 3.0 ± 0.2 × 10 -4 cm 2 mJ -1 under UVA and from 9.4 ± 0.4 × 10 -4 to 1.1 ± 0.1 × 10 In the UVA/H 2 O 2 process, goes from 2.2 ± 0.2 × 10 -5 to 3.5 ± 0.3 × 10 -5 cm 2 mJ -1 with 46 to 64% of the degradation achieved by oxidation. These close results are attributed to similar photolysis constants of the estrogens (Table 7) and similar second order rate constants (from 1.8 to 2.9 × 10 10 M -1 s -1 ) between HO • and the estrogens [9]. When using S 2 O 8…”
Section: Estrogen Degradation In Drinking Water In Various Aopssupporting
confidence: 62%
“…Then, another alternative is the use of solar light as a UV source. Incident solar radiation on earth is a free and renewable energy, composed of 95% of UVA and 5% of UVB and it was previously reported in the literature that UVA radiation is able to photolyse H 2 O 2 and S 2 O 8 2- [9,10]. Fernandes et al [11] also recently demonstrated that natural solar radiation is efficient in activating these oxidant precursors.…”
Section: •-mentioning
confidence: 99%
“…Given the fragility of the O–O bond, , we examined the effects of the wavelength of UV light used in irradiation. An aqueous solution of 7-OE and H 2 O 2 was oxidized under three wavelengths: UVC, UVB, and UVA .…”
Section: Methodsmentioning
confidence: 99%
“…Hence a new class of metal-based nanoadsorbents/heterogeneous catalysts with a better redox activity, photocatalytic nature in the visible band (400-700 nm), and economically feasible materials (e.g., Fe, Mn, Al) need to be studied as near-futuristic research and innovation technologies. Recently, a few research groups developed a new approach of metal ion activated external oxidants (Peroxymonosulfate: PMS, Persulfate: PS) in generating reactive radical species (i.e., sulfate radicals) for remediating various organic contaminants (e.g., estrogenic compounds) [53,54]. A recent article on reviewing the light-induced advanced oxidation processes (AOPs) as PFAS remediation methods are detailed elsewhere [32], whereas the present work focuses on light-induced, electrochemical supported [electro-oxidation] AOPs in addition to the electro-kinetic/coagulation-sorption.…”
Section: Figure 1 Pfas Cycle Illustrating Their Ubiquitous Presencementioning
confidence: 99%